Serological Diagnosis of Dengue Fever and Its Correlation with Platelet Counts In a Tertiary Hospital, Nellore, Andhra Pradesh, South India - M. Shabnum; P. Sreenivasulu Reddy; P. Vasundhara Devi (Highlights on Medicine and Medical Research Vol. 15, 2021)
Dengue fever is a mosquito-borne Arboviral infection that mostly affects tropical and subtropical countries around the world. Outbreaks occur almost every year due to a lack of immune prophylaxis and specific antiviral therapy. Rapid diagnosis is needed to avoid morbidity and mortality. Classical Dengue fever presents with sudden onset of fever, severe headache, chills, generalized muscle and joint pains. The aim of this study to know the seroprevalence of dengue virus in a tertiary care hospital, Nellore. Serological tests were performed on blood samples submitted in the microbiology lab from suspected dengue infections between June and October 2015. Dengue Day 1 Test kit (J. Mitra & Co. Pvt Ltd) was used to detect NS1 antigen, IgG, and IgM antibodies using a solid phase immunochromatographic technique. NS1 antigen positivity was found in 88.69% of the samples, 3.41% for IgM, and 2.77% for IgG. Thrombocytopenia was found in 71.42% of patients, with the highest rate in those who were just positive for the NS1 antigen (301 cases). Immunochromatography is the preferred test for making an accurate diagnosis since it combines antigen and antibody assays on a single serum sample and is simple and quick to perform.